A study on visual acuity and visual skills among presumed slow learners in primary school in Kota Bharu, Kelantan - Nor, Muzaliha Mohamed (2010)
The issues of slow learner have become a matter of increasing personal and public concern. In ability to read and write is a major obstacle to learning and may have social and economic implications. Those students who experience learning difficulties may also experience a treatable visual difficulty in addition to their primary learning difficulties. To detennine the visual acuity and visual skills among presumed slow learners in primary schools in Kota Bharu, Kelantan. We also studied the possible association between visual acuity and visual skills. A school based cross sectional study carried out from January 2009 to April 2010. Multistages cluster sampling was performed on all primary schools in Kota Bharu. Ocular examinations were carried out in all selected students. Visual acuity and visual skills were measured in 1010 students (average 9.5 years) in 20 primary schools. Participating students had been identified by their school teachers as presumed slow learners. Standard visual skills test and published norms were used. Majority of the students (96.5%) had good visual acuity in both eyes. There were only 4.5% of the students had visual impainnent. The main cause for poor visual acuity was due to refractive errors. There were 7.8%, 3.3% and 2.0% of the students had bilateral myopia, astigmatism and hypennetropia respectively. Most of them were undiagnosed and untreated before. Divergence skills and saccadic tracking skills were the most affected visual skills in this study population. Near point of convergence, convergence skills, accommodative amplitude and accommodative facility were still good. There was statistically significant association between the level of visual acuity and the level of convergence break and accommodative facility. There were no statistically significant association noted between the level of visual acuity and the level of convergence recovery, divergence break and recovery, amplitude of accommodation and saccadic tracking skill. The results showed large numbers of the presumed slow learner students had poor visual skills but less numbers of poor visual acuity. There were statistically significant association between the level of visual acuity and the level of visual skills.